2000
DOI: 10.1093/emboj/19.22.6207
|View full text |Cite
|
Sign up to set email alerts
|

Structure and mechanism of activity of the cyclic phosphodiesterase of Appr>p, a product of the tRNA splicing reaction

Abstract: The crystal structure of the cyclic phosphodiesterase (CPDase) from Arabidopsis thaliana, an enzyme involved in the tRNA splicing pathway, was determined at 2.5 A Ê resolution. CPDase hydrolyzes ADPribose 1¢¢,2¢¢-cyclic phosphate (Appr>p), a product of the tRNA splicing reaction, to the monoester ADPribose 1¢¢-phosphate (Appr-1¢¢p). The 181 amino acid protein shows a novel, bilobal arrangement of two ab modules. Each lobe consists of two a-helices on the outer side of the molecule, framing a three-or fourstran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
61
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 47 publications
(84 reference statements)
7
61
0
Order By: Relevance
“…This hypothesis was supported by the crystal structure (11,12) and a mutagenesis study with CPDase (S. cerevisiae) (4). Based on the current results, it is absolutely clear that these four residues are essential for the catalytic reaction since variation in either one of the four positions leads to almost complete reduction of interaction enthalpy.…”
Section: Functional Characterizationsupporting
confidence: 68%
See 2 more Smart Citations
“…This hypothesis was supported by the crystal structure (11,12) and a mutagenesis study with CPDase (S. cerevisiae) (4). Based on the current results, it is absolutely clear that these four residues are essential for the catalytic reaction since variation in either one of the four positions leads to almost complete reduction of interaction enthalpy.…”
Section: Functional Characterizationsupporting
confidence: 68%
“…The cloning strategy for PDase Homolog/RNA ligase from E. coli was similar to the one used for the yeast CPDase, using E. coli DNA and appropriate PCR primers; this protein was also expressed from a construct with pET28. All three proteins carried C-terminal hexa-histidine tags and were purified by affinity chromatography using a Ni 2ϩ -nitrilotriacetic acid resin as described in (11).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In close spatial vicinity of the tandem histidine motif (His88 and His148) are two acidic residues (Glu99 and Glu125). Such pairings of acidic with histidine residues have previously been observed in enzymatic sites, which also includes phosphoesterases (Hofmann et al, 2000b).…”
Section: Introductionsupporting
confidence: 64%
“…In particular, protease activity has been suggested as a shared feature of PR-1 proteins based on structure-function inference from the cone snail protease Tex31 (Milne et al, 2003), but could not be demonstrated to date. We were intrigued by the structural similarity of the tandem histidine motif of Group 1 ASPs with enzymatic sites found in phosphodiesterases such as the Arabidopsis CPDase (Hofmann et al, 2000b), and thus investigated the possibility that Na-ASP-2 might possess phosphohydrolase activity.…”
Section: Enzymatic Activitymentioning
confidence: 99%